Psychological Well-being and Its Predictors among Doctors in Tertiary Care Hospitals of Rawalpindi and Islamabad, Pakistan : Psychological Well-being and Its Predictors among - Sultan, Muhammad Abdullah; Siddiqui, Sohaib Haroon; Zedi, Syeda Qudsia; Khurshid, Saba; Mitha, Ayesha Abubakar (Pakistan Journal of Health Sciences, 2026)
Psychological well-being (PWB) is a very important aspect of doctors’ lives since their work is associated with a lot of stress. In Pakistan, the area has not been frequently studied to understand how PWB, as a multidimensional concept, appears among the doctors. Objectives: To assess the psychological well-being and factors affecting it among medical professionals working in tertiary care hospitals of Rawalpindi and Islamabad, Pakistan. Methods: A cross-sectional study was carried out among 385 doctors recruited through convenience sampling from April to June 2025 online-based structured questionnaire comprising sociodemographic information and the Ryff Psychological Well-Being Scale. Participant characteristics and well-being scores were summarized using descriptive statistics. Predictors of psychological well-being were identified using multiple linear regression analysis (p<0.05). Results: Among 385 doctors, 52.7% were male, and 47.3% were female. Descriptive analysis showed higher psychological well-being scores for Personal Growth (14.1 ± 2.6), Autonomy (13.7 ± 2.8), and Self-Acceptance (12.9 ± 2.7), with a total well-being score of 65.8 ± 11.5. The regression analysis revealed that marital status (β = 0.19, 95% CI [0.96, 4.26], p=0.002) and duty hours per day (β = –0.25, 95% CI [–4.66, –1.28], p=0.001) emerged as significant PWB predictors. Gender, age, years of service, and department were found to be non-significant predictors. Conclusions: Moderate psychological well-being was reported by doctors working in tertiary care hospitals, which was impacted by marital status and duty hours. It is advised to improve doctors’ well-being and their professional performance through the use of workload management, institutional support, and mental health programs.